Evaluating Unscheduled Readmission to Emergency Department in the Early Period - Abdullah Cüneyt Hocagil; Hilal Hocagil; Fikret Bildik; İsa Kılıçaslan; Hasan Karabulut; Ayfer Keleş; Ahmet Demircan (Balkan Medical Journal, 2016)
Background: The readmission in the early period (RAEP) is defined as the admission of a patient to emergency department (ED) for the second time within 72 hours after discharge from the ED.